2000
DOI: 10.1002/hep.510310125
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic preconditioning reduces Na+ accumulation and cell killing in isolated rat hepatocytes exposed to hypoxia

Abstract: Short periods of ischemia followed up by reperfusion are known to protect the heart against injury caused by a subsequent sustained ischemia. This phenomenon, known as ischemic preconditioning, has also been recently shown to reduce ischemic liver damage, but the mechanisms involved are still unknown. By using isolated hepatocytes as an in vitro model of liver preconditioning, we have investigated the possible effect of preconditioning on intracellular pH and Na ؉ homeostasis. Freshly isolated rat hepatocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
51
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 44 publications
(102 reference statements)
3
51
1
Order By: Relevance
“…8 Indeed, the V-ATPase inhibitor, bafilomycin A 1 , abolished the cytoprotection and reverted the effects of preconditioning of hepatocyte pH and Na ϩ levels. 8 Nonetheless, other mechanisms might also contribute to the development of cellular resistance to hypoxia and reoxygenation damage in preconditioned livers. For instance, Yadav and coworkers have shown that preconditioning prevented hepatocyte and endothelial-cell apoptosis by inhibiting caspase 3 activation.…”
mentioning
confidence: 96%
See 4 more Smart Citations
“…8 Indeed, the V-ATPase inhibitor, bafilomycin A 1 , abolished the cytoprotection and reverted the effects of preconditioning of hepatocyte pH and Na ϩ levels. 8 Nonetheless, other mechanisms might also contribute to the development of cellular resistance to hypoxia and reoxygenation damage in preconditioned livers. For instance, Yadav and coworkers have shown that preconditioning prevented hepatocyte and endothelial-cell apoptosis by inhibiting caspase 3 activation.…”
mentioning
confidence: 96%
“…In accordance to the in vivo experiments, hepatocyte preconditioning develops following a transient hypoxia lasting more than 5 minutes and not exceeding 10 minutes. 8 Moreover, we have observed that the prevention of intracellular acidosis and of cytosolic Na ϩ increase during hypoxia is responsible for reducing hypoxic injury in preconditioned hepatocytes. 8 These effects have been ascribed to the activation of H ϩ extrusion by vacuolar proton-ATPase (V-ATPase) that, by reducing hypoxic acidosis, limited Na ϩ influx promoted by the operation of Na ϩ /H ϩ exchanger and Na ϩ -HCO 3 -cotransporter.…”
mentioning
confidence: 97%
See 3 more Smart Citations